Western frontier of the Archaic Scythia: typo-chronology vs radiocarbon dating - Grechko, Denis (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2023)
One of the key issues in the chronology of Late Hallstatt period is the so-called Hallstatt plateau in the calibration curve extending the calibrated range of single dates to c. 800-400 BC. Analysis of the 14C dates of the ash-hill from the Chotyniec hillfort, indicate its dating to the time range, which does not exceed the interval of 780-469 BC. Typological analysis of the artefact collection allows us to date the ash-hill to the middle of the 7th – the first third of the 6th century BC (HaС2-HaD1). This dating corresponds to the Early Scythian time and chronology of the Western Podillian group. The analysis of material culture allows us to indicate the immediate closeness of the Chotyniec agglomeration to the Western Podillian group.
il. ; 25 cm
Keywords: archeologia; Central Europe; Tarnobrzeg Lusatian Culture; East European Forest-Steppe groups; Late Hallstatt period; chronology; typo-chronology; radiocarbon dating